QR-based Channel Estimation for Orthogonal Frequency Division Multiplexing Systems - Peilong Jiang; Honggui Deng; Bin Lei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Channel estimation is the key technology for Orthogonal Frequency Division Multiplexing (OFDM),  which has direct impact on the performance of OFDM. In this paper, we present a novel QR-based algorithm to update the channel impulse response(CIR) for DFT-based channel estimation. The discrete Fourier transform(DFT) estimation reduces the noise power that exists outside of the CIR part, because the estimated CIR from LS has most of its power concentrated on the first L samples. To reduce the noise power that exists inside of the first L samples, the CIR is further processed by QR decomposition in proposed algorithm. The simulation results show that the bit-error-rate(BER) of our estimator has reduced significantly compared with the conventional DFT-based channel estimator and LS-linear estimation.